PROBLEMS AND PERSPECTIVES OF COMPUTERIZATION OF BANKS AUDIT IN THE CONDITIONS OF DIGITAL ECONOMY (INNOVATIVE ECONOMY, 2020)
Koshchynets M.I., Spyak H.I., Khorunzhak N.M. PROBLEMS AND PERSPECTIVES OF COMPUTERIZATION OF BANKS AUDIT IN THE CONDITIONS OF DIGITAL ECONOMYPurpose. The aim of the article is the theoretical substantiation and practical solution of tasks related to the development of audit areas, improvement of its methodology and development of the structure and formalization of indicators.The tasks to be solved include the study of the essence, the identification of peculiarities of computer auditing in the banking sector, the analysis of managerial inquiries to choose the most problematic and important plot (the object of audit), as well as the development of the stages of its implementation and formalization of indicators on the selected object of audit.Methodology of research. General scientific and special methods are used in the process of research, in particular: abstract and logical (for clarification of the essence of computer auditing), system analysis (to identify the features of the audit with the use of computers, tools and methods for its implementation), statistical analysis and economic and mathematical modelling (when selecting an object of audit and formalization of evaluation indicators), complex analysis (when forming conclusions and suggestions for solving set tasks).Findings. The problems of computerization of audit in the banking sphere are identified, and the author’s vision of their solution is proposed. The essence of the concept “computer audit” is specified and its features are determined. The approach to the choice of the audit object is proposed, the stages of carrying out of audit procedures concerning non-performing loans are substantiated.Originality. The method of selecting the objects of audit, as well as the formalization of the evaluation indicators of its implementation, was further improved.Practical value. The obtained results of the research can be used by banks in the process of auditing with the use of computers, in particular, with regard to the selection of audit objects, substantiation of the stages of its implementation and formalization of the evaluation indicators.Key words: computer audit; audit procedures; means and methods of audit; object of audit; stages for audit implementation; formalization of evaluation indicators.
Keywords: Key words; computer audit; audit procedures; means and methods of audit; object of audit; stages for audit implementation; formalization of evaluation indicators.